Reinforcement sensitivity theory: a metatheory for biosocial criminology - Walsh, Anthony (Routledge advances in criminology, 2019)
Biosocial criminology : the paradigm for the twenty-first century -- A question for all ages : the hedonic tug of war -- Behavioral genetics : genes and heritability -- The human brain -- The canonical neurotransmitters and hormones -- Molecular genetics and the environment -- Anomie/strain, learning theories, and the adolescent brain -- The control tradition and human nature -- The antisocial personalities : psychopaths and sociopaths -- The schizophrenia spectrum and crime -- Attention-deficit/hyperactivity disorder -- Criminal violence -- Index